Factors Influencing Decisions to Purchase Halal Products for Ptkis Students in Cianjur Regency - Farid Faisal; Uus Ahmad Husaeni; Reksa Jayengsari; Farid Faisal (Prodi Ekonomi Syariah Universitas Majalengka, 2023)
This study aims to analyze the factors influencing the decision to purchase halal products for students of private Islamic religious colleges (abbreviated PTKIS) in the Cianjur Regency. The research method used in this research is quantitative. The variables used are halal certification, awareness, and food composition as the independent variables, and the decision to purchase halal products as the dependent variable. This study's population was PTKIS students in the Cianjur Regency area. The number of PTKIS students in Cianjur Regency who filled out the questionnaire was 142. Meanwhile, the data analysis technique uses multiple linear regression. This study concludes that halal certification influences the decision to purchase halal products for PTKIS students in Cianjur Regency. Halal awareness influences the decision to purchase halal products. Meanwhile, food composition has no significant effect on purchasing decisions for halal products. Halal certification is an essential key for business product development. Halal awareness among PTKIS students has a significant influence on purchasing decisions. Meanwhile, most students do not use food composition as the primary reference when choosing halal products.